RANCANG BANGUN SISTEM PENJADWALAN DAN KONTROL KANDANG KELINCI BERBASIS INTERNET OF THINGS - Alie Sulthan, Mayben Sayyidina; Divayana, Yoga; Rahardjo, Pratolo (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p29, 2023)
These days technology has developed rapidly, almost covering all aspects in humas life for example is automation system. The automation system works without human intervension and complete all works independently. Existing technology can already be connected to each other via the internet network so that it can transmit or receive data automatically. The Internet of Things (IoT) can support automated systems by providing real-time information so that users can monitor the performance of these automated systems. This research was to develop rabbit cage by utilizing microcontroller as monitoring system. The system utilizing Internet of Things (IoT) as monitoring medium between users and devices to help users monitor their rabbit cage remotely. The design installed several sensors such as ultrasonic, temperature, load cell sensors, DS18B20 and water level sensors. This research used Arduino Mega 2560 as main microcontroller and NodeMCU ESP8266 as communication device between the tools and database. The tools use android application on user smartphone that fuctions real time monitoring for the cage. Based on the results of this research by using Arduino Mega as microcontroller board to controlling and monitoring rabbit’s cage has succesfully in monitoring the cage via internet through the NodeMCU ESP8266 intermediary according to the design.